Peningkatan Pengetahuan Kader Posyandu Terkait Pemberian Makan Bayi Dan Anak (PMBA) - Putra, Muh Guntur Sunarjono; Sarwono, Amalia Shalihat Fauziyah (LPPM Universitas Timor, 2025)
The magnitude of the nutritional problem in Indonesia, based on the results of the 2023 Indonesian Health Survey, shows that the prevalence of stunting is 21.5%, wasting is 8.5%, and underweight is 15.9%. Adequate intake for under-aged children is achieved by good feeding practices to meet energy and nutritional needs in terms of quantity and quality, as reflected in complementary foods for breast milk. Community service related to feeding babies and children was conducted at Posyandu Asoka V on Wednesday, April 17, 2024, which 15 people attended. This nutrition education uses the lecture method and power points—evaluation in measuring target understanding using pre-test and post-test questionnaires. The series of Community Service activities include giving pre-test questions, delivering material related to feeding babies and children and ending with giving post-test questions. As a result of this activity, nutrition education can increase the subject's knowledge score regarding infant and child feeding with a post-test score (after being given education) 50.6 points greater than the pre-test score (before being given education).